The Impact Of Social Media Marketing Activity On Purchase Intention: Brand Awareness As A Moderator In An Intercity Bus Study - Olfebri; Yuliantini; Cecep Pahrudin (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The optimization of social media in public transportation facilities such as public buses is increasingly being improved. So far, empirical research that examines the role of Social Media Marketing Activity (SMMA), Brand Awareness (BA), and Purchase Intention (PI) in one model at the same time in the perspective of Uses and Gratification Theory (UGT) is very limited. This study aims to examine the role of SMMA as an antecedent to BA and PI, as well as the contribution of BA as a moderator to the influence of SMMA on PI in the UGT perspective. This study obtained 262 answers from respondents who are intercity and interprovincial bus users and actively use Facebook as social media to get information about Public Buses. Data was collected using a questionnaire with a convenience sampling approach. The hypothesis that has been proposed in this study is entirely accepted with the direction of influence being entirely positive. This study reveals that SMMA is able to provide alternatives in answering user needs, the optimization of SMMA can trigger the dual role of BA as an internal and external factor in increasing the PI of public buses.